Academic-humanitarian partnerships: leveraging strengths to combat COVID-19. Issue 1 (31st December 2020) - Aluisio, Adam R.; Zhu, Emily; Gil, Gabriela; Kenyon, Thomas; Uzevski, Vlatko; Levine, Adam C
ABSTRACT: The Coronavirus Disease 2019 (COVID-19) pandemic has overwhelmed many health systems globally. Innovative initiatives are needed to combat the pandemic and scaleup response efforts. This communication describes a collaborative partnership between an international humanitarian organization and an academic university to develop and rapidly deploy a remote digital COVID-19 trainer-of-trainers (TOT) program to enhance global response. The ongoing program has resulted in more than 900 TOT personnel who have themselves trained over 22, 000 frontline response providers from 21 different countries and territories. The developed and implemented COVID-19 digital training program is a key example of how academic-humanitarian partnerships can be leveraged to strengthen healthcare training and response capacity during pandemics.